(untitled) (Journal of Enam Medical College, 2020)
Background: Urinary tract infection (UTI) is the most common illness affecting both males and females in almost all age groups. Hence, continuous analysis of prescribing pattern in UTI is vital. Objective: The study was designed to determine the prescribing pattern of antibiotics in UTI patients at a tertiary care hospital. Materials and Methods: A prospective observational study was carried out on 180 patients in Dhaka National Medical College Hospital from January to March 2012 by collecting data from outpatient department of Surgery, Medicine and Gynaecology & Obstetrics. Results: Analysis of prescribed drugs revealed that use of antibiotics such as nitrofurantoin (30.55%), cefuroxime (22.22%) and ciprofloxacin (16.66%) were significantly higher compared to other drugs. The most common isolated organisms were Escherichia coli (60%), Proteus (20%), Klebsiella (13.33%), and Pseudomonas (6.66%). Conclusion: Present findings are suggestive of the need for periodic monitoring of antibiotic sensitivity pattern to provide effective treatment. J Enam Med Col 2020; 10(1): 23-26